Interleukin-21 gene polymorphisms in Iranian multiple sclerosis subjects - Ahmadloo, Salma (2012)
Multiple Sclerosis (MS) as an autoimmune inflammatory disease which affects the central nervous system (CNS), is reportedly the second most widespread culprit for neurological disability among young adults. Ranging between 2 and 150 per 100,000, MS is prevalent everywhere in the world. In recent years, the increasing incidence of MS in Iran has been a matter of interest for investigators. Even though MS cannot be claimed to be directly hereditary, genetics variants are reportedly related with MS. Cytokines play an important role in the initiation and maintenance of autoimmune diseases including MS. As a new pro-inflammatory cytokine, interleukin-21 (IL-21) has recently been observed as a target of intervention in many autoimmune diseases such as MS. On the other hand, IL-21 is a cytokine that is produced by T helper 17 (Th17) cells and functions as a growth factor for Th17 cells, considering the importance of IL-21 in Th17 cells development as a new central pathogen in MS disease also new finding on the role of IL-21 in MS disease, association of IL-21 gene polymorphisms (C5250T and G1472T) with MS disease in Iranian subjects were investigated. In this study 301 Iranian MS patients (224 females and 77 males) with mean age of 33.26 +/- 8.74 Years and 201 healthy controls (149 female and 52 male) with mean age of 32.4 +/-8.64 were used to determine the G1472T polymorphism in the second intron (rs2055979) and C5250T polymorphisms in the Exone 3 (rs4833837) of IL- 21 gene. Among patients under study, information related to disease type, EDSS score, Progression Index and age of disease onset were obtained. IL-21 G1472T polymorphism was identified by RFLP-PCR method while the IL-21 C5250T polymorphism was genotyped via allele specific oligonucleotide PCR (ASO-PCR). Genotype and allele frequencies were compared between patients and controls by chi-square. Association of polymorphisms with disease types, age at disease onset, EDSS score and progression index were also investigated. Genotype and Allele frequencies at +1472 G/T position were compared between normal population and patients group. On evaluation of genotypes and allele frequency at this position, there was a significant difference between cases and controls (p=0.003). Also, association of type of disease with G1472T polymorphism was analyzed and a significant difference in genotype frequency was observed between patients and controls group (p=0.0001). The association of G1472T polymorphism with EDSS, progression index and onset age were not significant (p=0.8, p=0.35, p=0.16, respectively). At +5250 C/T position among 301 patients under study, genotype distribution was determined Differences between cases and controls was not significant (p=0.95). Of the 310 patients studied at +5250 C/T position, type disease was determined in 223 patients. Statistical analysis showed no significant difference between genotype frequency and disease type (p=0.71). The association of C5250T with progression index, EDSS and age at disease onset, were not significant (p=0.8, p=0.35 and p=0.16, respectively). In conclusion this study showed that IL-21 gene polymorphism (G1472T) was significantly associated with MS development. Other studies to clarify the association of this polymorphism with MS susceptibility in other populations would be desired.